Diffuse Large B Cell Lymphoma, Bilateral Lower Extremity Lymphedema, and Ulcerated Inguinal Lymph Node - NATA PRATAMA HARDJO LUGITO; ANDREE KURNIAWAN; THEO AUDI YANTO (National Cancer Center - Dharmais Cancer Hospital, 2014)
Lymphedema (LE) is a chronic medical condition characterized by lymphatic fluid retention, resulting in tissue swelling. There are two general classifications of LE; primary and secondary which are based on two mechanisms; lymphatic obstruction and lymphatic interruption. The most common cause of LE in the developing world is secondary to an infection known as filariasis. Cancer including Hodgkin and non-Hodgkin lymphomas; and its treatment are some causes of secondary LE. LE also could maintain the persistence of an occult localization of lymphoma. This case illustration describes a female, 57 year-old with stage II lymphedema of both legs, bilateral inguinal lymphadenopathies that were biopsied. The filarial blood examination was negative. Biopsies showed diffuse large B-cell lymphoma.